Diseño y manufactura de un handbike híbrido (2020)
The design and manufacture of a hybrid handbike for a user with paraplegia was developed. The design of the handbike is based on the desires and needs of the user, considering his physical condition and the ergonomics of the device. It was possible to manufacture and test the prototype. It met the requirements established at the beginning of the design process. Because of this, it allows the user to travel autonomously around the city. Likewise, the user has the possibility of exercising by making use of this device, improving his quality of life.--Taken from the Degree Document Format.